Explosive fragmentation of Prince Rupert’s drops leads to well-defined fragment sizes - Stefan Kooij; Gerard van Dalen; Jean-François Molinari; Daniel Bonn (Nature Communications, 2021)
Fragmentation of breaking glass as a brittle solid is a problem of equal practical and theoretical importance. Kooij et al. demonstrate that the fragment size distribution can surprisingly be both, either power-law or exponential, depending on how a particular specimen is broken.